Helraiser intermediates provide insight into the mechanism of eukaryotic replicative transposition - Ivana Grabundzija (Nature Portfolio, 2018)
Helitrons are eukaryotic DNA transposons that have profoundly affected genome variation due to their ability to capture and mobilize host genomic fragments. Here the authors provide insight into the mechanism of action of these transposons both in cells and in vitro.